A New Subclass of Meromorphic Close-to-Convex Functions. (8th January 2013) - Soni, Amit; Kant, Shashi
Abstract : A new subclass MK (t, A, B ) of meromorphic close-to-convex functions, defined by means of subordination, is investigated. Some results such as inclusion relationship, coefficient inequality, convolution property, and distortion property for this class are derived. The results obtained here are extension of earlier known work.